PELAKSANAAN KURIKULUM TINGKAT SATUAN PENDIDIKAN PADA MADRASAH ALIYAH NEGERI I PONTIANAK - Mulyani Mudis Taruna (Balai Penelitian dan Pengembangan Agama Semarang, 2008)
This research was done at Madrasah Aliyah Negeri I in Pontianak,the capital of Western Borneo. The focus of the research was the implementation of Education Unit Level Curriculum (KTSP) at MadrasahAliyah Negeri I Pontianak which was seen from the aspects of the implementation of KTSP itself, of the management, of the administration ofthe management, of developmental method, of learning facilities, and ofthe evaluation of learning system. In addition, this research also examined how learners' perceptions of the implementation of KTSP were.From the result of the research showed that the implementation ofKTSP at Madrasah Aliyah Negeri I Pontianak could run well in accordance with learning procedure, namely operationally the curriculumhad been composed by the education unit itself with various kinds ofdynamism although it did not free from the standard of content whichwas composed by BSNP (National Education Standard Agency). Similarly, learners' perceptions showed that they understood enough andwere able to follow the learning process with KTSP as the new curriculum after the application of KBK (Competency Based-Curriculum).However, on another side, there were several disadvantages whichneeded improvement such as human resources factor, namely teacherswho had experience in local level but lacked insight into communication in national level, frequent occurrences of technical obstacles in theimplementation, insufficient facilities for the learning process such asincomplete multimedia and the existing learning media if they were connected to the ratio of learners, a high shortage of teachers' handbooksso that on average teachers only mentioned 2 reference books namely Ipackage book and I book published by Toha Putra Semarang and prac tically the supervision of education has not yet been done by counselorsfrom Regional Office of Ministry of Religious Affairs of Pontianak.